DESIGN OF BELT CONVEYOR FOR CORN COB SHELLER AND CHOPPER MACHINE - Rachmat, Asep; Albaar , Alwi; Budiman; Kusumadewi, Intan; Sonjaya, Cecep (Universitas Majalengka, 2024)
The use of a belt conveyor is one of the choices of facilities or tools used to transport or move materials or as a means of transporting materials, both bulk materials and individual materials. One of the machines that requires a conveyor is a corn cob sheller and chopper machine which was created in 2022. by Majalengka University students. This tool has a problem, namely, the corn that has been shelled cannot automatically go straight into the chopping machine, so a design is needed that takes into account the safety factor and the correct conveyor speed. This is of course for safety and ensures that the conveyor can transport corn which has a density of 760 kg/m 3 at a slope of 300 ‰. For this reason, the conveyor that best suits these needs must have specifications with a total belt length of 0.295 m, drum pulley diameter of 3 in or 0.0762 m, shaft diameter of 20 mm with a length of 500 mm, 150 watt electric motor drive, 16T small sprocket gear and 24T large sprocket with chain number 35. Safety Factor (SF) on the Belt Conveyor frame has a minimum SF value of 6.3, with a maximum tension of 32.5 N/mm2 and yield strength of 204 N/mm2 and a belt speed of 0.5 m/s.